Pemeriksaan Kesehatan Gratis Pada Masyarakat Di Masa Pandemi COVID-19: Pemeriksaan Kesehatan Gratis Pada Masyarakat Di Masa Pandemi COVID-19 - Desria Mauliati (Ahmar Metakarya: Jurnal Pengabdian Masyarakat, 2022)
The behavior of clean and healthy living in the community before the COVID-19 pandemic was still low, which consisted of the habit of washing hands with soap, consuming healthy food, physical activity, adequate rest, clean water, proper sanitation, not smoking, and others. When the covid-19 pandemic occurred, Indonesian people who had various social characteristics, ranging from age group, education level, economic status, exposure to the internet/mass media, social environment, culture, ethnicity and others had diverse understandings and attitudes towards the Covid-19 pandemic, the understanding and attitudes formed can affect the actions/behavior of the community, not all community members comply with the health protocol. The health problem that often occurs in the local community is that hypertension is a public health threat because of its potential to cause complications such as stroke, coronary heart disease and kidney failure. The purpose of this service is to increase community compliance with health protocols and to find out the results of blood pressure checks in order to prevent and treat these health problems. The method used in this activity is by giving announcements and gathering the community in the meunasah yard of Ie Suum Village and immediately holding free health checks for 23 people who come. The result of this service is that it is carried out properly and smoothly in accordance with the activity plan that has been prepared, this activity received a very good response from the community with the activeness and presence of the community to take part in the free health check-up activity by not leaving the activity before the end of time. It is hoped that after this activity the community can realize the importance of maintaining health, especially as a preventive program from health problems that occur especially during the Covid-19 pandemic.